2020
DOI: 10.2217/bmm-2020-0254
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Albumin Levels Predict Risk for Nonsurvivors in Critically Ill Patients with Covid-19

Abstract: Aim: We aimed to explore the biomarkers for disease progression or the risk of nonsurvivors. Materials & methods: This study included 134 hospitalized patients with confirmed COVID-19 infection. The outcome of moderate versus severe versus critically ill patients and survivors versus nonsurvivors were compared. Results: An increase in the severity of COVID-19 pneumonia was positively associated with lower levels of platelets and albumin (all p < 0.05). In the critical group, the plasma levels of albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 25 publications
6
63
1
1
Order By: Relevance
“…Seventeen of these studies were from various COVID-19-designated hospitals in Wuhan City, which was the most infected area in China [2][3][4]8,[10][11][12][13][14][15][16][17][18][19][20][21] . There was also a nationwide multicenter study supported by the National Health Commission of China that enrolled 1099 patients from 552 hospitals in 30 provinces 6 .…”
Section: Epidemiology Of Covid-19-associated Acute Kidney Injurymentioning
confidence: 99%
“…Seventeen of these studies were from various COVID-19-designated hospitals in Wuhan City, which was the most infected area in China [2][3][4]8,[10][11][12][13][14][15][16][17][18][19][20][21] . There was also a nationwide multicenter study supported by the National Health Commission of China that enrolled 1099 patients from 552 hospitals in 30 provinces 6 .…”
Section: Epidemiology Of Covid-19-associated Acute Kidney Injurymentioning
confidence: 99%
“…A case series by Liu et al demonstrated that increasing eosinophils may be an indicator of improvement in the COVID-19 disease [ 40 ]. It has also been noted that hypoalbuminemia is a predictor of mortality, independent of age and comorbidity burden [ 41 ]. Furthermore, a rise in neutrophil/lymphocyte count and neutrophil/platelet count may point towards a heightened risk of myocardial injury and mortality [ 42 ].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Age, comorbidities, c-reactive protein, albumin, cytokine, lactate dehydrogenase, D-dimer, albumin, platelet, lymphocyte, neutrophil, smoking, cough, expectoration, chest pain, dyspnea, CT manifestations, et al, have been reported to be associated with the severity of COVID-19 in some small studies in China, [15][16][17][18][19][20][21] and other countires. 13,22,23 Jiangsu, a province in China over 600 km from Hubei without common geographical borders and 80 million population, reported over 600 patients infected with COVID-19.…”
mentioning
confidence: 99%